The Urgency of the State as Amil Zakat: Study of the Thought of Prof Sjechul Hadi Permono - Ghozali, Muhammad Lathoif; Himami, Fatikul; Saoki, Saoki (El-Qish: Journal of Islamic Economics, 2024)
This research aims to reveal how important the position of the state is in managing zakat funds. Little research has been conducted on the repositioning of the state after the state established a representative amil body. The recognition of individual amil was made legal in the Constitutional Court decision in 2012, in addition to the National Amil Zakat Agency as a representation of state amil, private institutions, and individual amil. However, the intervention of state amil is eroding in reality and experiencing a crisis of trust in the community. This reality is worrying, considering that state amil is very urgent and is wajibat al-manziliyah in the management of zakat. Therefore, by using a library research approach (literature research) and emphasizing gronder theory-based content analysis, this research produces important findings, namely first, in the responsibility of Sultan al-ijtimaiyah, the state has full authority to ensure justice in the management of zakat. Second, the state is positioned as ahlu al-halli wa al-'aqdi to make policies and provide sanctions with the intention of management (collection, management, and distribution) of zakat running optimally, and third, the state has mainstreaming in the management of zakat, as an authority that has policies, decisions and rule makers.